CitySDK Tourism API - building value around open data. Issue 1 (August 2015) - Pereira, Ricardo; Sousa, Pedro; Barata, Ricardo; Oliveira, André; Monsieur, Geert
Abstract Tourism is a major social and cultural activity with relevant economic impact. In an effort to promote their attractions with tourists, some cities have adopted the open-data model, publishing touristic data for programmers to use in their own applications. Unfortunately, each city publishes touristic information in its own way. A common Application Programming Interface (API) for accessing this information would enable applications to seamlessly use data from several cities, increasing their potential market while reducing the development costs. This would help developers in making cross-city applications, lowering the overhead of supporting new cities and providing them with increased exposure. Finally, tourists will also benefit from better and cheaper applications due to the boosted competition. This paper provides an overview of the design, deployment and utilization of the CitySDK Tourism API, which aims to provide access to information about Points of Interest, Events and Itineraries. It was designed in order to be used by municipalities, regional or national governments as well as other public or private entities interested in publishing touristic information. The API comprehends a delegation model, allowing applications to access worldwide information by only knowing a single API endpoint. The API was created and validated in the context of the CitySDK project, through which a server reference implementation, client libraries and a set of demonstration applications have also been made available. The API is currently available for the cities of Amsterdam, Helsinki, Lamia, Lisbon and Rome. Several companies have developed mobile applications that use this API.